The Development a Product of KoyPed dessert from Alhumdulillah Rice flour - Kanjanarak, Patthama; Sirinthip Suttapong; Dudsadee Supbua; Punfujinda, Chaiyasit; Chumkaew, Krittin (Journal of Thai Food Culture, 2025)
This research aimed to study the standard recipes of KoyPed dessert (Crispy Roll) and to study appropriate ratio of Alhumdulillah rice flour in KoyPed dessert (Crispy Roll). The researchers researched 3 accepted recipes of Crispy Roll. After that, 5 food experts were tested using a sensory quality test 9 – point hedonic scale found that the 3rd recipes received the most favorable scores from experts ranking in high level (7.38). Then develop the 3rd recipe into KoyPed dessert from Alhumdulillah rice flour. Alhumdulillah rice flour was used to replace rice flour at 3 levels which are 30, 50 and 100 percent of the total rice flour weight then testing consumer preferences. The population and sample were 50 personnel and students of Suan Dusit University, Trang Center. Then analyze statistical variance and compare the mean differences. Sensory quality assessment results found that the use of Alhumdulillah rice flour in place of rice flour at a ratio of 30 percent of rice flour weight were highest accepted level with highest preferences of overall score of 7.52. The differences were statistically significant (p≤0.05) The results of the color measurement showed that the increasing of Alhumdulillah rice flour resulting in more brightness (L*) of red (a*) and yellow (b*) which resulting in stronger color of the products. Hardness Force found that increasing the amount of Alhumdulillah rice flour make KoyPed dessert (Crispy Roll) crispier and harder at statistically significant (p≤0.05). Also found that using Alhumdulillah rice flour instead of rice flour at the percentage of 30 with Moisture value and Aw value at the lowest level however there was no statistically significant difference (p≤0.05) with another 2 recipes.